عضو البرلمان الجزائري بين التمثيل الوطني والحزبي - لصلج, نوال (جامعة الوادي University of Eloued, 2017)
تعالج هذه المقالة إشكالية توفيق عضو البرلمان الجزائري بين مهامه كممثل وطني لمجموع أفراد الشعب المنصوص عليها دستوريا وبين مهمته كممثل لحزبه لأن أعضاء البرلمان تحكمهم تكتلات حزبية ولا يستطيعون الخروج عـما تمليه عليهم أحزابهم وإلا اعتبروا متمردين علــى توجيهات الحزب ويمكن أن يصل الأمر إلى حد توقيع جزاءات لقاء هذا التمرد، فإلى أي مدى يستطيع عضو البرلمان الجزائري التوفيق بين هاذين الاتجاهين؟. Summary: This article treats the two problem or the problem set of the Algerian parliamentary member in order to create an harmony between his mission as a national representative of the people individual group enacted by the constitution and between his mission as a representative of his party because the parliamentary members are governed by a partisan blocs and they cannot avoid their parties instructions otherwise they will be considered rebellious for their party recommendations the case can reach until the signature of punishments per contra of this rebellion, so how the Algerian parliament can create an harmony between these two currents?
Keywords: التمثيل النيابي؛ عضو البرلمان؛ الشعب؛ الناخب؛ الحزب السياسي